The Importance of Migraine Lalophobia and its Association With Other Symptoms and Comorbidities - Piovesan, Elcio Juliato; Utiumi, Marco Antonio Takashi; Bernardes, Arthur Feliphe Strutt; Zolet, Henrique Miotto; Kowacs, Pedro Andre (Headache Medicine, 2023)
Full abstract in PDF.